ANALYSIS OF THE RELATIONSHIP BETWEEN BANK CREDIT AND EU ECONOMIC GROWTH FOR THE PERIOD 2010-2020 - Waleed Ashour Khaleed (Scholar Express Journals, 2024)
The research focused on analyzing the relationship between bank lending and economic growth of the European Union (EU-27) for the period from 2010 to 2020, using the GMM model. This model allows solving problems of serial correlation, heteroskedasticity and homoscedasticity of some explanatory variables. As the results show, savings promote growth. Inflation and bank credit have a negative impact on economic growth as in previous studies.
Keywords: Economic; Inflation; Bank Credit